2010
DOI: 10.1007/bf03395734
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control and Impulsiveness in Nondieting Adult Human Females: Effects of Visual Food Cues and Food Deprivation

Abstract: Self-control can be defined as the choice of a larger

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Studies of time discounting were also divided between stated and revealed preference studies, with the stated preference studies including tasks such as hypothetical choice between sooner-smaller and later-larger rewards (Hoefling & Strack, 2010; Li, 2008; Rasmussen, Lawyer, & Reilly, 2010; Wang & Dvorak, 2010), and the revealed preference studies included incentive compatible choice between sooner-smaller and later-larger rewards (Forzano & Chelonis, 2010; Kirk & Logue, 1997; Kuhn et al, 2014; Logue & King, 1991).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of time discounting were also divided between stated and revealed preference studies, with the stated preference studies including tasks such as hypothetical choice between sooner-smaller and later-larger rewards (Hoefling & Strack, 2010; Li, 2008; Rasmussen, Lawyer, & Reilly, 2010; Wang & Dvorak, 2010), and the revealed preference studies included incentive compatible choice between sooner-smaller and later-larger rewards (Forzano & Chelonis, 2010; Kirk & Logue, 1997; Kuhn et al, 2014; Logue & King, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Third, some studies investigate whether people are more impatient—preferring a smaller reward sooner over a larger reward later—as a function of glucose. As in the prior two cases, tools used to investigate impatience—or an individual’s discount rate—rely on either explicit choices, such as subjects choosing between two hypothetical rewards (Wang & Dvorak, 2010) or more indirect methods relying on revealed preferences (Forzano & Chelonis, 2010; Kirk & Logue, 1997; Kuhn, Kuhn, & Villeval, 2014; Logue & King, 1991; Reuben, Sapienza, & Zingales, 2010). Fourth and finally, work on “decision style” investigates whether people are more “intuitive” as opposed to “deliberate” in their decision making when glucose levels are low.…”
Section: Glucose Effects On Behavior and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐control can also be depleted by the very act of making a decision, leaving cognitive resources subsequently unavailable to make thoughtful choices (17). Notably, the presence of food cues can deplete self‐control in both dieting and non‐dieting individuals, causing them to eat larger quantities of food (20–22).…”
Section: Decision‐making: Automaticity Dual Process Theory and Neuromentioning
confidence: 99%
“…In Mischel and Ebbesen's (1970) delay-of-gratification experiment, voluntary waiting time in children between the ages of 3.5 and 5.7 years was substantially increased when rewards were absent versus visible. In addition, Forzano and Corry (1998) and Forzano et al (2010) showed that exposure to visual food cues influenced many adult women's impulsivity.…”
mentioning
confidence: 99%